The neuroendocrine puzzle of epilepsy and infertility: what are we missing? - Kobylarek, Dominik; Zakryś, Katarzyna; Gierszewska, Julia; Pagidela, Bhavana Reddy; Lan, Yung-Yi; Kovinthapillai, Rujith; Rajczewski, Aleksander; Kozubski, Wojciech; Michalak, Sławomir (Frontiers in Neurology, 2025)
Epilepsy, a chronic neurological condition affecting over 70 million individuals worldwide, has far-reaching effects beyond seizure activity, including a significant impact on reproductive health by posing significant challenges to fertility and hormonal health. Emerging evidence underscores the complex bidirectional interplay between epilepsy, antiepileptic drugs (AEDs), and sex steroid hormones; particularly progesterone, testosterone, and prolactin, which influence both seizure threshold and reproductive function. This paper explores how epilepsy alters hypothalamic–pituitary-gonadal (HPG) axis dynamics, often leading to conditions like polycystic ovary syndrome (PCOS), anovulation, and menstrual irregularities. Moreover, the role of prolactin dysregulation following seizures, as well as the impact of temporal lobe epilepsy on gonadotropin-releasing hormone (GnRH) pulsatility, is examined in relation to infertility outcomes. By integrating current research on neuroendocrine signaling and reproductive physiology, this paper highlights the need for individualized care strategies in individuals with epilepsy to optimize both seizure control and reproductive health.